Numerical study on the effects of using metal foam filled elliptic cooling channel and TEG on the energy/exergy performance of PV module - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2025)
Development of novel cooling systems are crucial for efficient operation of photovoltaic (PV) integrated energy systems. In the current study, a novel cooling system that uses metal foam filled elliptic cooling channels boosted with hybrid nanofluid and thermoelectric generator (TEG) module is proposed. Assessment of cooling system on the energy and exergy performance of PV unit are numerically performed by using Galerkin weighed finite element method. The numerical study is conducted for different values of the following: aspect ratio (AR between 0.25 and 1.5), number of cooling channels (Nc between 4 and 8), size of the cooling channels (rc between 0.001r0 and 0.85r0), and loading of nanoparticles in the base fluid (between 0 and 2%). Average PV-cell temperature decreases with increasing cooling channel numbers; the effect is more pronounced at lower aspect ratios. Energy and exergy efficiency increase with increasing aspect ratios and number of cooling channels. While the tendency for better potential IP is in the opposite direction, increased cooling channel numbers result in higher SI. Without any cooling, the energy and exergy efficiencies of PV modules are 13.8% and 11.1%, respectively. The values are 14% and 11.5% when TEG is utilized, and 15.5% and 13.3% when TEG+metal foam filled channel with hybrid nanofluid is used. Sustainability index (SI) and improvement potential (IP) are 1.12 and 3.11, without cooling system, however with a cooling system that has a TEG+metal foam filled channel boosted with nanofluid, they are 1.15 and 2.95. As compared to 3D-high fidelity coupled simulations, satisfactory agreement between the energy and exergy efficiencies of PV system with TEG+channel cooling system is obtained by utilizing the polynomial model.
Keywords: Metal foam; PV cooling; Thermoelectric unit; Exergy; FEM; Sustainability